Complex Regional Pain Syndrome (CRPS Type II) After Carpal Tunnel Release Surgery: Case Report - Hakan Tunç; Sibel Ünsal Delialioğlu; Canan Çulha; Sumru Özel (Galenos Yayinevi, 2010)
Summary Complex regional pain syndrome is a chronic syndrome characterised with dystrophic changes and neurovascular disordes of bone and skin of extremities. The most common etiological factors are trauma, ischemic heart disease, cerebral lesions, servical region disorders, infections, and surgical treatments. Carpal tunnel syndrome is the most common compressive neuropaty of the upper extremity. There are various surgical and conservative alternatives in the treatment of carpal tunnel syndrome. Complex regional pain syndrome has been reported as a complication of surgical carpal tunnel release in 2-5% of patients. In this case report clinical characteristics and rehabilitation outcomes of a patient with complex regional pain syndrome after carpal tunnel release surgery is presented. (Osteoporoz Dünyasından 2010;16:41-3)